Electron scattering analysis in 2DEG in sputtering-grown MgZnO/ZnO heterostructure. (14th January 2020) - Kumar, Pawan; Khan, Md Arif; Siddharth, Gaurav; Kumar, Sanjay; Singh, Ruchi; Mukherjee, Shaibal
Abstract: Here, we present an analytical modeling of electron mobility in two dimensional electron gas (2DEG)-yielding MgZnO/ZnO heterostructures, to ascertain dominant scattering mechanisms and physical parameters responsible for one-order lower value of electron mobility in sputtering-grown heterostructure as compared to that in molecular beam epitaxy-grown heterostructure. This work extensively probes all scattering components and their physical parameters, such as dislocation density, impurity density, mole fraction, 2DEG density, correlation length and lateral size, for their respective effects on electron mobility of sputtered heterostructure. The results suggest that dislocation density and alloy disorder scattering are the most dominant sources responsible for reduced electron mobility. This work is extremely crucial for achieving high electron mobility by optimizing the material growth parameters to attain low dislocation density, impurity density and interface roughness, for the development of low-cost ZnO-based heterostructure field effect transistors.